Assessing the Relationship of Human Development Index (HDI) and Government Expenditure on Health and Education in Selected ASEAN Countries - Lantion, Danielle Ann; Musñgi, Gabrielle; Cabauatan, Ronaldo (International Journal of Social and Management Studies, 2023)
Various studies exhibited the importance of government spending in developing human capital. It can enhance income distribution and employment opportunities, reduce extreme poverty, and increase the consumption of essential services like healthcare and education. The study aims to analyze the relationship between government spending on education and healthcare on the Human Development Index (HDI) of five Southeast Asian countries: the Philippines, Thailand, Malaysia, Indonesia, and Singapore, using the Panel Least Squares method. The study proves that government expenditure on education significantly and positively impacts HDI. In contrast, government spending on health exhibits a positive yet statistically insignificant influence on HDI. These findings imply that directing resources toward education efficiently enhances human capital in the examined countries. However, the same efficiency does not hold true for government allocation to health.